Integrated Strategies for Controlling Flower Thrips in Southern Highbush Blueberries - Oscar E. Liburd; H. Alejandro Arevalo (EDIS, 2019)
There are a number of thrips species that damage blueberries in North America. Flower thrips are among the most important insect pests that attack early-season blueberries. This document is IPM-140, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date November 2005.